EFFECTIVENESS OF SILVER DIAMINE FLUORIDE AND PROPOLIS FLUORIDE VARNISH APPLICATION ON DENTIN WITHIN 60 DAYS - SOEKANTO, SRI ANGKY; DAYANARA, PRISCILLA; DAVIQ, HABLI; SARWONO, AGOENG TJAHAJANI; SAHLAN, MUHAMAD (International Journal of Applied Pharmaceutics, 2019)
Objective: This study sought to analyze the effectiveness of silver diamine fluoride (SDF) and propolis fluoride (PPF) varnish application on dentin within 60 days. Methods: We divided 60 blocks (4 mm × 4 mm × 2 mm) of human permanent teeth dentin specimens into six time-based groups: 0 days, 1 day, 7 days, 14 days, 30 days, and 60 days. We then applied 20 μL SDF and PPF varnish to the specimens’ occlusal surfaces. For the fluoride test, all specimens were submerged in deionized water, while for the flavonoid test, specimens were submerged in a solution of 20% ethanol. In the treatment group, specimens were shaken for 30 min at 45 rpm (every day) for 0–60 days, depending on group assignment. An ion selective electrode was used to measure fluoride ions and a spectrophotometer with 425 nm wavelength absorbance measured flavonoid absorbance. Dentin microhardness was measured for 30 and 60 days sample using the Vickers microhardness tester. Results: There was an increase in fluoride ion concentration after SDF and PPF application to the dentin samples, while SDF released more fluoride ions than PPF. Increased flavonoid absorbance was observed after PPF application. Dentine microhardness increased after SDF and PPF application. Conclusion: SDF and PPF application on dentin is effective within 60 days.